Modeling Patterns of Negative Life Events and Mental Health in Faroese Adolescents - Petersen, Tóra; Armour, Cherie; Elklit, Ask (Scandinavian Journal of Child and Adolescent Psychiatry and Psychology, 2013)
Objectives: The objective of this study was to identify naturally occurring typologies of Faroese adolescents on the basis of their exposure to traumatic and negative life events. It was hypothesized that underlying typologies of trauma and negative life events would be uncovered. Furthermore, it was hypothesized that males would be overrepresented in classes characterized by the endorsement of a wide range of trauma and negative life events. On the basis of prior research, it was also hypothesized that females had endorsed more traumas of a sexual nature and that males had endorsed more traumas of a violent nature. Finally, post-traumatic stress, negative affectivity, and somatization were examined in the different typologies. Methods: Latent class analyses were conducted with the use of data collected from a self-report questionnaire survey from 687 Faroese eighth graders (85% response rate). The questionnaire included a traumatic and negative life event list, the Harvard Trauma Questionnaire—Part IV, and the Trauma Symptom Checklist. Results: Three classes of adolescents were identified on the basis of their exposure to potentially traumatic and negative life events. The baseline class (81.3%) had a low probability of the endorsement of all potentially traumatic and negative life events, except threats of violence and bullying. This group had low scores for post-traumatic symptoms, negative affectivity, and somatization. Class 2 (13.7%) comprised mainly males and had the highest probability of endorsement of threats of violence, physical assault, and bullying; this group also had high scores for post-traumatic stress symptoms, negative affectivity, and somatization. Finally, Class 1 (5.0%) consisted of adolescents with a relatively high risk of exposure to all potentially traumatic events and negative life events, except threats of violence. This group had the highest scores for post-traumatic stress symptoms, negative affectivity, and somatization. Conclusions: The present study can be said to be a concise picture of trauma exposure and its consequences among Faroese adolescents, and it is thereby a valuable tool for the national planning of preventive and interventional strategies and for empirically founded economic prioritization. These results emphasize the importance of choosing a trauma-informed strategy in various disciplines, such as pediatrics, child and adolescent psychiatry, social work, and school psychology when the aim is to provide the appropriate intervention.